An Improved, Practical, and Scalable Five-Step Synthesis of Psilocybin - Sherwood, Alexander M.; Meisenheimer, Poncho; Tarpley, Gary; Kargbo, Robert B. (Synthesis, 2020)
Described herein is an improved synthesis of 3-[2-(dimethylamino)ethyl]-1H-indol-4-yl dihydrogen phosphate (psilocybin). The protocol outlines: synthesis of multigram quantities of psilocybin, identification of critical in-process parameters, and isolation of psilocybin without the use of chromatography, TLC, or aqueous workup. The synthesis furnishes psilocybin in five steps in 23% overall yield from an inexpensive acetoxyindole starting material. With specific focus on process control and impurity fate and removal, the improved procedure is amenable to providing high-quality psilocybin.
Keywords: psilocybin; psilocin; phosphorylation; hydrogenolysis; reduction; quenching method; major depressive disorder